MANAGEMENT OF SUSTAINABLE URBAN DEVELOPMENT IN MODERN CONDITIONS - Anastasia PANDAS; Oleg POPOV (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2020)
The development of the city's economy is a continuous the process of changing its socio-economic state. The key to the successful development of the city is a successful combination of competent strategic and tactical management of urban development with the widespread introduction of innovative projects aimed at increasing the economic, social and environmental component of the city. The problems of managing sustainable urban development are currently relevant, and urban policy should be developed based on a reliable scientific and methodological foundation. In the current ecological and economic conditions for the development of cities, the need to develop a concept of sustainable development that meets the economic needs of the population and business and contributes to the protection of the natural environment is actualized. The development of sustainable development strategies for cities opens up new opportunities for the rational and efficient use of all types of resources, finding a balance of interests between social, environmental and economic factors of development, between the authorities, business and society. Also, the achievement of sustainable urban development can be facilitated by various directions of institutional, economic, environmental transformations, such as scientific substantiation and definition of criteria, principles and mechanisms for achieving environmentally sound management, development and improvement of the institutional, organizational, economic, social and technological foundations of the innovative development of urban agglomerations, as well as the development of schemes for the formation of an effective business-oriented urban environment in order to stimulate sustainable development